Taxing Mobile and Overconfident Top Earners - Andreas Haufler; Yukihiro Nishimura (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We set up a simple model of tax competition for mobile, highly-skilled and overconfident managers. Firms endogenously choose the compensation scheme for managers, which consists of a fixed wage and a bonus payment in the high state. Managers are overconfident about the probability of the high state and hence of receiving the bonus, whereas firms and governments are not. In this setting we show that overconfidence (i) unambiguously increases the bonus component in the managers' compensation package and (ii) it reduces the bonus tax rate that governments set in the non-cooperative tax equilibrium. Hence overconfidence can contribute to explaining both the increasing role of bonus contracts and the fall in marginal tax rates for high-income earners.
Keywords: H20; H87; G28; 330; overconfidence; bonus taxes; tax competition; migration